Multi-omics of permafrost, active layer and thermokarst bog soil microbiomes - Hultman, Jenni; Waldrop, Mark P.; Mackelprang, Rachel; David, Maude M.; McFarland, Jack; Blazewicz, Steven J.; Harden, Jennifer; Turetsky, Merritt R.; McGuire, A. David; Shah, Manesh B.; VerBerkmoes, Nathan C.; Lee, Lang Ho; et al. (Nature (London), 2015)
A multi-omics approach, integrating metagenomics, metatranscriptomics and metaproteomics, determines the phylogenetic composition of the microbial community and assesses its functional potential and activity along a thaw transition from intact permafrost to thermokast bog. Multi-omics survey of frozen-soil microbiomes The application of the various individual 'omics' tools to the study of microbial ecosystems has dramatically altered our view of their constituents and ecology over the past decade. Here Janet Jansson and colleagues develop an multi-omics approach, integrating metagenomics, metatranscriptomics and metaproteomics to analyse microbial gene expression in frozen soils that form part of the Alaska Peatland Experiment. The results show that the community shifts along a natural thaw gradient from permafrost to seasonally thawed active layer to thermokarst bog and the authors find that there is a transition in the potential for several biogeochemical cycles with thaw, including those for denitrification, nitrate reduction, iron reduction and methane oxidation. Over 20% of Earth’s terrestrial surface is underlain by permafrost with vast stores of carbon that, once thawed, may represent the largest future transfer of carbon from the biosphere to the atmosphere 1 . This process is largely dependent on microbial responses, but we know little about microbial activity in intact, let alone in thawing, permafrost. Molecular approaches have recently revealed the identities and functional gene composition of microorganisms in some permafrost soils 2 , 3 , 4 and a rapid shift in functional gene composition during short-term thaw experiments 3 . However, the fate of permafrost carbon depends on climatic, hydrological and microbial responses to thaw at decadal scales 5 , 6 . Here we use the combination of several molecular ‘omics’ approaches to determine the phylogenetic composition of the microbial communities, including several draft genomes of novel species, their functional potential and activity in soils representing different states of thaw: intact permafrost, seasonally thawed active layer and thermokarst bog. The multi-omics strategy reveals a good correlation of process rates to omics data for dominant processes, such as methanogenesis in the bog, as well as novel survival strategies for potentially active microbes in permafrost.